2019
DOI: 10.1088/1742-6596/1305/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Polymer gel-based measurements of the isocenter accuracy in an MR-LINAC

Abstract: As magnetic resonance-guided radiotherapy (MRgRT) is becoming increasingly important in clinical applications, the development of new quality assurance (QA) methods is needed. One important aspect is the alignment of the radiation and imaging isocenter. MR-visible polymer gels offer a way to perform such measurements online and additionally may allow for 3-dimensional (3D) evaluation. We present a star shot measurement irradiated and scanned with a 0.35 T MR-LINAC device evaluating the polyacrylamide gelatin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A recent study demonstrated the coincidence of radiation and imaging isocenter in 3D for a conventional Linac with an onboard kV-CBCT (Adamson et al 2019). A first isocenter alignment measurement at a 0.35 T MR-Linac-System was presented by Dorsch et al (2019), however, this study used a suboptimal MR sequence with a slice thickness of 20 mm to generate a sufficiently high signal at this low field strength. The 2D image had a low signal-to-noise ratio and did not allow for isocenter alignment measurements in 3D.…”
Section: Measurement Of Isocenter Alignment Accuracy and Image Distor...mentioning
confidence: 99%
“…A recent study demonstrated the coincidence of radiation and imaging isocenter in 3D for a conventional Linac with an onboard kV-CBCT (Adamson et al 2019). A first isocenter alignment measurement at a 0.35 T MR-Linac-System was presented by Dorsch et al (2019), however, this study used a suboptimal MR sequence with a slice thickness of 20 mm to generate a sufficiently high signal at this low field strength. The 2D image had a low signal-to-noise ratio and did not allow for isocenter alignment measurements in 3D.…”
Section: Measurement Of Isocenter Alignment Accuracy and Image Distor...mentioning
confidence: 99%
“…It is not sufficient to solely test each system independently; checks applicable to both systems simultaneously are desirable. An example of such integrated tests would be the isocentricity check, which ensures that the isocentres of the MR, RT and, if used, laser system match within tolerance [15] . It is desirable to verify the integrity of the oMRgRT treatment chain, beginning with image acquisition for offline treatment planning, generation of the baseline treatment plan, patient / phantom setup, online imaging and treatment application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, like other 3D gel dosimeters, favorable characteristics are a good temporal stability, a high spatial integrity, a low temperature sensitivity and low dose rate dependence. We found that a Methacrylic Acid based polymer gel dosimeter [6] has a high dose-R2 sensitivity and satisfies most of the aforementioned criteria.…”
Section: Introductionmentioning
confidence: 89%
“…Polymer gel dosimeters (PGDs) based on 6% (w/w) methacrylic acid and 8% (w/w) gelatin, referred to as MAGAT, were fabricated according to a recipe discussed elsewhere [6]. Four different sets of phantoms were fabricated: 14 test tubes that served as calibration vials, two 1L cylindrical flasks (diam.…”
Section: Manufacturing Of the Polymer Gel Dosimetermentioning
confidence: 99%